Global Animal Law: What It Is and Why We Need It. Issue 1 (10th March 2016) - Peters, Anne
Abstract: The symposium collection in this issue of TEL, consisting of four articles including this framing article, seeks to conceptualize and flesh out a new branch of law and legal research: global animal law. The starting hypothesis is that contemporary animal law must be global or transnational (that is, both transboundary and multilevel) in order to be effective. In times of globalization, all aspects of (commodified) human−animal interactions (from food production and distribution, working animals and uses in research, to breeding and keeping of pets) possess a transboundary dimension. Animal welfare has become a global concern, which requires global regulation. This foreword introduces the three symposium articles, sketches out the research programme of global animal law and links its emergence to the ongoing 'animal turn' in the social sciences, including political philosophy.